Pengaruh Motivasi, Penghargaan Finansial, dan Pertimbangan Pasar Kerja terhadap Minat untuk Berkarir Sebagai Akuntan - Made Sri Rejeki Arthasari; Cokorda Gde Bayu Putra (UNHI Press, 2022)
According to the International Federation of Accountants, what is meant by the Accounting Profession is all fields of work that use expertise in the field of accountants, including public accountants, internal accountants working in industrial, financial or trade companies, accountants working for the government or accountants as educators. This paper was conducted by targeting Accounting Professional Education Students, Faculty of Economics and Business, Udayana University. All students of the accounting profession are defined as the population. The research sample is 46 people, and analyzed by regression technique. Observations found a result where students' interest in becoming an accountant could be influenced by self-motivation (motivation), financial rewards, and consideration of the available job market later. The results of this study indicate that motivation has an effect on the interest of students in accounting profession education to become accountants. Financial awards affect the interest of students in the Accounting Profession to become Accountants. Labor market considerations affect the interest of students in the Accounting Profession to become Accountants